2019
DOI: 10.1111/ncmr.12153
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation Contexts: How and Why They Shape Women's and Men's Decision to Negotiate

Abstract: In the substantial body of research on gender differences in the initiation of negotiation, the findings consistently favor men (Kugler et al., 2018). We propose that this research itself is gendered because negotiation research has traditionally focused on masculine negotiation contexts. In the current study, we replicate the gender effect in initiating negotiations (favoring men) and provide an empirically based selection of “masculine,” “feminine,” and “neutral” negotiation contexts, which can be used for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 59 publications
2
35
1
3
Order By: Relevance
“…In the project, we investigated students' propensity to initiate negotiations about their grades as well as motives, perceptions, and expectations about the negotiation. Two publications already emerged based on the data collected in this project: Reif and Brodbeck (2017) and Reif et al (2019). The analyses presented in this paper were not addressed by either of these publications.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the project, we investigated students' propensity to initiate negotiations about their grades as well as motives, perceptions, and expectations about the negotiation. Two publications already emerged based on the data collected in this project: Reif and Brodbeck (2017) and Reif et al (2019). The analyses presented in this paper were not addressed by either of these publications.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the disproportionate number of men's and women's opportunities to practice negotiating (resulting from gendered role expectations and thus a different frequency of exposure to negotiation situations) also might result in women's lower expectancy considerations in negotiations. Research showed that women in general tend to be less confident than men (Watson & Hoffman, 1996) and have less self-efficacy regarding their negotiation ability compared to men (Reif et al, 2019;Stevens, Bavetta, & Gist, 1993). Thus, a possible explanation of gender differences on the initiation of negotiation may lie in gendered expectancy considerations:…”
Section: Expectancies As Mediators Of Gender Differences In the Initimentioning
confidence: 99%
See 3 more Smart Citations